2010
DOI: 10.1108/09526861011010686
|View full text |Cite
|
Sign up to set email alerts
|

Quality control methods at a hospital

Abstract: Past studies considered the application of various statistical process control techniques for improving healthcare quality. The study extends research by employing process improvement efforts to understand and develop medical record assembly in a regional hospital via process flow diagramming and control charts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Health care costs continue to increase and stewardship of blood must be considered, because of the high costs of RBC transfusion and RBC shortages that have been observed in multiple jurisdictions . In multiple areas of health care, quality improvement strategies have been used successfully to improve resource use and deliver quality to the end user . This has been applied to single‐unit transfusion strategies, reflected in the recent articles and abstracts described in our review assessing the effect of promotion of single‐unit transfusion strategies or other patient blood management related interventions generally demonstrating benefit.…”
Section: Discussionmentioning
confidence: 99%
“…Health care costs continue to increase and stewardship of blood must be considered, because of the high costs of RBC transfusion and RBC shortages that have been observed in multiple jurisdictions . In multiple areas of health care, quality improvement strategies have been used successfully to improve resource use and deliver quality to the end user . This has been applied to single‐unit transfusion strategies, reflected in the recent articles and abstracts described in our review assessing the effect of promotion of single‐unit transfusion strategies or other patient blood management related interventions generally demonstrating benefit.…”
Section: Discussionmentioning
confidence: 99%
“…Amongst these applications are: monitoring the level of radiation received by the patients under treatment (Waterhouse, Smith, Assareh, & Mengersen, 2010), decreasing in-hospital mortality intensive care unit (Koetsier, de Keizer, de Jonge, Cook, & Peek, 2012), signalling the outbreak of post eye surgery infectious (Chiam & Feyi-Waboso, 2009), control charts for healthcare surveillance (Jiang, Shu, Zhao, & Tsui, 2013;Joner, Woodall, Reynolds, & Fricker, 2008), monitoring rare health events such as needle stick injury (Fatahi, Noorossana, Dokouhaki, & Moghaddam, 2012), reducing patient turnaround time (Kao, 2012), controlling out-ofhospital cardiac arrest patient mortality (Chen, Chung, Hu, Fan, & Yang, 2011), medical 2 O. Rasouli and M.H. Zarei records assembly process (Canel, Mahar, Rosen, & Taylor, 2010), and applications in nursing practices (Polit & Chaboyer, 2012). Woodall (2006) reviewed different applications of control charts in healthcare based on the type of charts deployed.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the discussion regarding the implementation of quality control to support health services has also begun to be discussed. [4] conducted a study on the implementation of quality control in hospitals and found that quality control can improve hospitals' service processes. [5] applied process capability analysis and simulation to enhance process flow in hospitals.…”
Section: Introductionmentioning
confidence: 99%